Dissecting the causal relationship between neuroticism and osteoarthritis: a univariable and multivariable Mendelian randomization study - Zhang, Shuren; Ji, Junhui; Zhang, Zexia; Cui, Zhichao; Su, MeiHua (Frontiers in Psychiatry, 2024)
Background: Mental health has been found to be associated with risk of osteoarthritis, but the causal relationship was not fully clarified.Methods: Two-sample Mendelian randomization (MR) study was conducted to investigate the causal relationship between neuroticism (n=329,821) and the two most frequently affected parts of osteoarthritis (OA) (knee OA: case/control = 24,955/378,169; hip OA: case/control = 24,955/378,169) using large scale summary genome-wide association study (GWAS) data. Inverse variance weighted (IVW), weighted median, and MR-Egger were used to estimate the causal effects. Multiple sensitivity analyses were conducted to examine the robustness of the causal estimates.Multivariable MR (MVMR) analysis was used to estimate the direct effects of neuroticism on OA after accounting for the other OA risk factors. Two-step MR approach was employed to explore the potential mediators of the causal relationship.Results: Univariable MR analysis indicated that 1-SD increase in genetically predicted neuroticism score was associated with an increase risk of knee OA (IVW OR:1.17, 95%CI: 1.087-1.26, p=2.72E-05), but not with hip OA. The causal effects remained significant after accounting for the effects of BMI, alcohol drinking, vigorous physical activity, but being attenuated with adjustment of smoking. Further mediation analysis revealed that smoking initiation mediated a significant proportion of the causal effects of neuroticism on knee OA (proportion of mediation effects in total effects: 22.3%, 95%CI: 5.9%-38.6%, p=7.60E-03).Conclusions: Neuroticism has significant causal effects on knee OA risk. Smoking might partly mediate the causal relationship. Further studies were warranted to explore the underlying mechanisms and potential use of neuroticism management for OA treatment.